Pengembangan Media Pembelajaran Kartu Tripet Pada Materi Hidrokarbon Kelas XI Di SMA Negeri 1 Bonti - Diana Nini; Hamdil Mukhlishin; Rizmahardian Ashari Kurniawan (Entalpi Pendidikan Kimia, 2026)
This study aims to develop a Triplet Card learning media for hydrocarbon material for Grade XI students of SMA Negeri 1 Bonti. The study employed the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were Grade XII students of SMA Negeri 1 Bonti who were involved in the media trial. The trials were carried out in two stages, namely a small-group trial involving 6 students and a large-group trial involving 30 students in one class. The instruments used consisted of validation sheets from material experts, media experts, and language experts, as well as response questionnaires for teachers and students. Data collection techniques were conducted through expert validation and the distribution of questionnaires in both trial stages. The results showed that the Triplet Card learning media obtained a high level of validity, with an average score of 88% for the material aspect, 93% for the media aspect, and 91% for the language aspect. The practicality test also indicated very positive responses, with 97% from the teacher and 88% from students. Thus, the Triplet Card is declared valid and practical based on the practicality test conducted.